Understanding risk factors of aggression behavior among illegal street racing (Mat Rempit): A review concepts - Hussin, Zalmizy (2014)
Research on risk factors of aggression behavior among illegal street racing has progressed to a point at which a unifying framework is needed. This article describes the risk factors that affecting participation among illegal street racing, or Malay called ‘Mat Rempit’ in aggression behavior.The term “risk factor” refers to any condition that may increase the likelihood of ‘Mat Rempit’ engage in aggressive behavior.This factor is dominated by the three dominant factors, namely individual, family, and peers.This article also explain Social Learning Theory by Akers and Sellers (2004) as a social behavioral approach to understand that phenomenon.